TRANSPORTER SELECTION STRATEGY FOR DELIVERY OF GOODS ACCORDING TO CUSTOMER NEEDS - Erfikhar Fadhlurrahman; Adi Budipriyanto (Sean Institute, 2023)
Current technology has developed very rapidly especially in the purchase of goods. Purchase of goods can now be ordered via online. The uniqueness of goods available on the internet or marketplace has varied. The more unique the item, the faster it will sell well. Delivery service is also needed to accommodate the delivery of goods. Because of the limitations of mobility, currently most people prefer to shop online rather than shopping directly to shopping centers. As online shop users, they will certainly hesitate in choosing a shipping service, and considering some factors in choosing shipping. Factors starting from the price, packaging of goods, shipping time, system services make users confused in choosing the best courier. The purpose of this study is to provide information to users in choosing the best shipping service by applying the Simple Additive Weighting method to calculate the case for selecting the type of goods delivery and physical analysis in purchasing goods online as a support for shipping goods.